Indicadores de Eutrofização na Represa Billings, São Paulo: Apoio ao Planejamento Urbano e à Gestão de Mananciais - Santos, Fabiano Sampaio Rodrigues dos; Ribeiro, Andreza Portella; Oliveira, Anderson de; Gallego, Jorge L (National Journal of City Management, 2025)
Objective: To assess water quality in the Billings Reservoir by calculating the Trophic State Index (TSI) using total phosphorus (TP) and chlorophyll-a (Chl-a) as indicators, in order to support urban planning and water resource management in the Metropolitan Region of São Paulo. Methodology: Analysis of secondary data from CETESB (2020-2022) for 9 monitoring stations regarding indicator quantification in samples collected during dry and rainy seasons. The relationship between TP and Chl-a was assessed through statistical inference tests, controlling for spatial variability among sampling sites. TSI was calculated according to Lamparelli’s (2004) methodology, and results were spatially distributed in thematic maps using QGIS software. Originality/Relevance: The study provides an updated diagnosis of one of Brazil’s most important water sources, supplying approximately 21 million inhabitants, while contextualizing institutional and socioeconomic constraints that hinder water resource management in the Metropolitan Region of São Paulo. Results: The reservoir exhibited predominantly supereutrophic and hypereutrophic conditions, with maximum TP and Chl-a concentrations of 510 µg/L and 511 µg/L, respectively, exceeding by up to 51 times the limits established by CONAMA Resolution 357/2005. ANCOVA confirmed that TP is the predominant factor in Chl-a variation (F=30.65; p<0.001). Sampling sites directly receiving water pumped from the Pinheiros River maintained the highest concentrations and TSI values, especially during the rainy season. Theoretical/Methodological Contributions: The integration of statistical analysis with TSI spatial distribution facilitates communication of technical results to public managers, constituting a replicable approach for assessing other urban reservoirs. Social and Environmental Contributions: The study provides an updated technical diagnosis supporting investment prioritization in basic sanitation and effluent treatment in the Billings basin. Quantification of the impact of Pinheiros River pumping on water quality offers elements for operational management decisions. The work also highlights the situation of irregular occupation ( 1 million people without adequate sanitation), supporting the development of watershed recovery programs aligned with SDGs 6 and 14 of the 2030 Agenda.